Sticky Prices: New Evidence from Retail Catalogs - Kashyap, A. K. (Quarterly Journal of Economics, 1995)
This paper presents new results on the size, frequency, and synchronization of price changes for twelve selected retail goods over the past 35 years. Three basic facts about the data are uncovered. First, nominal prices are typically fixed for more than one year, although the time between changes is very irregular. Second, prices change more often during periods of high overall inflation. Third, when prices do change, the sizes of the changes are widely dispersed. Both “large” and “small” changes occur for the same item, and the sizes of these changes do not closely depend on overall inflation.